The relationship between self-determination motivation and eating behaviour of obese students - Ahmad, Juwariah; Jamaluddin, Rahimah; Hamzah, Ramlah (Universiti Putra Malaysia Press, 2016)
The World Health Organization (WHO) (2008) reported that overweight and obesity are the fifth major risk for global deaths. At least 2.8 million adults die every year due to overweight or obesity. This study was performed to examine the relationship between motivation and eating behaviour among obese students. This quantitative study involved 400 form four and form five students with Body Mass Index (BMI) of 25.00 and above. This study was conducted in the Federal Territory of Kuala Lumpur. The data of this study were collected based on the Behavioral Regulation in Eating Questionnaire (BREQ) by Mullan, Markland and Ingledew (1997). Whereas the eating behaviour questionnaire was adapted from Child Eating Behavior Qestionnaire (CEBQ) (Santos, Gonzalez, Smalley, & Cataldo, 2011). The findings of this study clearly showed that self-determination motivation of the obese students was at a moderate level (M=3.12, SD=0.59). The results also clearly showed that there was a significant relationship between motivation and eating behaviour of the obese students. Majority of the respondent (76.0%) possessed moderate level of self-determination motivation. Those who possessed high self-determination motivation were around 17.3% (69 respondents) while those who possessed low self-determination motivation were around 68% (27 respondents). The findings indicate that, overweight students and students with obesity possessed moderate internal and external motivation towards healthy eating habit. They do not possessed high internal motivation towards healthy eating habit. They were also found failed to set their objectives towards achieving healthy eating habit. It was alarming since it is common for any individual to have high self-determination motivation in order to achieve their goals, which in this case, achieving a healthy eating habit. They do not require any external factors, such as other people in order to achieve their goals. They themselves should determine their objectives, and later try to achieve those objectives. This study suggests an r correlation coefficient of .114. Since the r correlation coefficient was significant (p<.05), it indicates that there was a significant positive relationship between self-determination motivation and healthy eating habit. The size of r correlation coefficient (r=.114) indicates a weak relationship between those variables.